Physical Characteristics of Coffee Beans from Steaming Processin Single Column Reactor (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
One of important steps in decaffeination process is steaming. The aim of steaming is to expand coffee beans porosity in order to obtain optimal condition for decaffeination process. Steaming can be done in single column reactor using saturated water vapour as media. The objective of this research is to study physical characteristics of coffee beans after steaming process using single column reactor. Material tested was Robusta coffee with 13—14% moisture content after dry processing. Reactor capacity is 6 kg dried coffee beans and 30 l water to produce water vapour. Dried coffee beans classified in 4 grades, i.e. diameter size (d) d>7,5 mm; 6,5